On the edge of empires - Palermo, Rocco, author.
1 online resource.
Keywords: "In antiquity, North Mesopotamia was the centre of the confrontation between different imperial entities. Rome, the Parthians, the Sasanians and the nomads of the region were all agents of a complex series of dynamics that impacted on the area: Rome found the most serious threat to its territorial control in the East in these lands, and the political turmoil of the region also affected daily life. This volume explores this mixed culture, unique in the Roman territories, combining literary and historical, and archaeological and environmental evidence in order to explore this important frontier between east and west"--